Currency unions and trade : what is the impact of the euro on trade in the euro area? - Tykkyläinen, Jasse (2012)
The aim of this study is to estimate the effect of the euro on trade within the euro area. This has been a relevant question for European politicians ever since the launch of the common currency was agreed on in the Maastricht Treaty in 1992. To analyse the topic the gravity model of international trade augmented with several dummy variables is employed using panel data of 29 developed countries between 1995 and 2010. The estimated aggregate trade effect on the euro zone reaches 10 % in the most preferred regression and is comparable with earlier estimates. However, there is considerable variation in the results when different sample sizes are used. This could be a sign of omitted variable bias that requires further in-depth analysis. Moreover, to help decision-makers correctly estimate the costs and benefits of the common currency additional research on trade effects in individual countries is desirable.